Breaking the Auditor’s Silence: Does CEO Openness Influence the Moral Courage of Internal Auditors? Evidence from Uganda - David Nyamuyonjo; Daniel Kipkirong Tarus; Joyce Komen (SEISENSE Business Review)
Purpose: Unethical behaviors such as fraud are continuously hurting organisations. Although internal auditors are expected to report unethical behaviours, such as fraud, when witnessed, some remain silent for fear of retaliation. Drawing on upper-echelon theory, this study examines whether the chief executive officer's (CEO's) openness is associated with internal auditors’ moral courage to speak out on ethical concerns. Design: This explanatory study collected data from 128 internal auditors in formal financial institutions using structured questionnaires and used partial least squares structural equation modeling to test the hypothesis. Findings: CEOs' openness to internal auditors' recommendations is positively associated with internal auditors’ moral courage. Practical implications: CEOs may appreciate listening to internal auditors as a way of motivating them to speak. Furthermore, boards of governors can encourage CEOs to show openness to internal auditor recommendations. Originality: This study adds to the scant empirical evidence on the factors that influence internal auditors’ moral courage. The empirical findings further confirm that contrary to the idea that internal auditors are independent of CEOs, CEOs influence internal auditors, thereby validating the broader applicability of upper-echelon theory.